The Impact of Environmental, Social, and Governance (ESG) Practices on Service Quality and Business Reputation in the Restaurant Industry - Haryadi Sarjono; Ine Silviya; Jang Jae Hyeok (Binus Business Review, 2025)
The food service industry plays a key role in the economy of a country. The research examined the impact of Environmental, Social, and Governance (ESG) practices on the service quality and reputation of tteokbokki restaurants in Korea and Indonesia. The research employed a quantitative and verification approach, utilizing a cross-sectional method that involved surveys and interviews with 30 respondents, including restaurant customers, business owners, and culinary industry professionals. The results show that ESG significantly improves service quality in both countries. However, the direct impact of ESG on reputation is only significant in Indonesia, while in Korea, service quality acts as the main mediator that influences reputation. This difference is due to regulatory and cultural factors, where Korean consumers prioritize service quality over ESG initiatives, while Indonesian consumers are more responsive to sustainability practices. These findings emphasize the importance of tailoring ESG strategies to local market expectations to maximize their impact. The research provides theoretical contributions by strengthening the relationship between ESG, service quality, and reputation and offers practical implications for industry players and policymakers. Moving forward, further research is needed to explore additional moderating factors, such as governance structure and consumer awareness levels, to deepen the understanding of the role of ESG in building business reputation across markets.